The Relationship Between Authoritarian Parenting and Psychological Well-Being in Adolescents - Fajri, Diva Widyawati Anggraeni; Kusumaningrum, Fitri Ayu (Unisia, 2024)
This study investigates the relationship between authoritarian parenting and adolescent psychological well-being, aiming to clarify how maternal and paternal practices influence developmental outcomes. The research was conducted with 200 adolescents aged 13–19 years, employing standardized measures of psychological well-being and parental authoritarian style. Data analysis included descriptive statistics, percentile-based categorization, assumption testing, correlation analysis, and additional tests based on demographic variables. The findings reveal significant negative correlations between authoritarian parenting and psychological well-being, with maternal authoritarian practices showing a stronger association than paternal practices. While the strength of the correlations was relatively weak, the results highlight that low responsiveness and high demandingness in parenting diminish adolescents’ self-acceptance, optimism, and supportive relationships. Intercorrelation analyses further demonstrated that maternal and paternal low responsiveness were most strongly linked with reduced well-being, while additional tests showed stronger effects among male adolescents and significant differences based on parental education level. These findings align with international research emphasizing the adverse consequences of authoritarian parenting, yet they also underscore the moderating role of cultural norms, socioeconomic factors, and gender. The study contributes to theoretical debates by illustrating how parenting styles intersect with demographic variables to influence adolescent well-being, while also providing practical implications for parenting interventions and school-based mental health programs. In conclusion, the results affirm the need for culturally sensitive approaches to parenting education and policy, and they encourage future longitudinal and cross-cultural research to further explore these complex dynamics.